Uma nova dinâmica: a impetração de Habeas Corpus, após a celebração de Acordo de Não Persecução Penal (ANPP), a fim de que seja reconhecida a atipicidade do fato - Alamy, Guilherme Alves Marques Höfke (2023)
The expansion of consensus spaces in the Brazilian criminal negotiating justice system is a reality that is increasingly accentuated as a trend of transformation of the current legal system, such as through the introduction of negotiating mechanisms, like the bargaining institute, which, in view of the anticipation of the punitive power by the confession of the accused, allows the application of a more mild penalty. In this context, after the enactment of Law nº 13.964/19 and the institution of the newest instrument of Negotiated Justice, the Non-Prosecution Agreement, new dynamics emerged to be experienced by the Brazilian legal system. Therefore, this paper intends, through the analysis of a decision of the Superior Court of Justice (STJ), namely the HC 619.751 monocratic decision, to verify the possibility of recognizing the atypicality of an act, due to the application of the principle of insignificance, in a criminal process in which a Non-Prosecution Agreement (ANPP) was signed, through a Habeas Corpus. The situation in question is fraught with issues of procedural and substantive law, as well as raising questions about the limitation of the importation of the principles of Negotiated Justice to Criminal Law, about the possibility of characterizing bad faith and procedural unfairness in the enjoyment of a right and whether the constitutional remedy would be the appropriate means to provoke the Judiciary in this situation. In light of this, the other arguments used were visited, as well as a brief analysis was made of the STJ's single decision in HC 698.186, which understood the viability of recognizing the insignificance of the conduct through the filing of the constitutional remedy, even after the execution of a Non-Prosecution Agreement, contrary to the aforementioned judgment. Thus, given the unprecedented nature of the situation at hand, the arguments that justify its (in)viability were evaluated and that, most likely, will also guide the continued construction of Negotiated Criminal Justice in Brazil, which has already proven to be a trend and is increasingly being embraced by the Brazilian legal system.